2019
DOI: 10.18202/jamal.2019.08.10018
|View full text |Cite
|
Sign up to set email alerts
|

Peran Beyond Budgeting Entry Scan Untuk Mengatasi Permasalahan Penganggaran Sektor Publik

Abstract: Peran Beyond Budgeting Entry Scan untuk Mengatasi Per masalahan Penganggaran Sektor Publik. Penelitian ini memiliki tujuan untuk mengidentifikasi dan menelaah permasalahan penganggaran pada Badan Layanan Umum (BLU) sebuah perguruan tinggi berdasarkan prinsip beyond budgeting. Metode yang digunakan adalah studi kasus terhadap sejumlah petinggi Politeknik Keuangan Negara STAN. Hasil penelitian menunjukkan bahwa berdasarkan Beyond Budgeting Entry Scan (BBES), terdapat tiga permasalahan utama penganggaran yakni ku… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 34 publications
1
5
0
5
Order By: Relevance
“…This study uses a single case study approach where it focuses on one phenomenon. Case study is the right method to answer certain phenomena or research problems deeply (Biswan & Widianto, 2019). This study uses case study to explore deeper research phenomena, as well as add insight into the occurrence of these phenomena.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study uses a single case study approach where it focuses on one phenomenon. Case study is the right method to answer certain phenomena or research problems deeply (Biswan & Widianto, 2019). This study uses case study to explore deeper research phenomena, as well as add insight into the occurrence of these phenomena.…”
Section: Methodsmentioning
confidence: 99%
“…A research by Kang & He (2018) stated that environmental management strategy is a company's effort to achieve performance with special abilities in obtaining and allocating resources that depend on environmental orientation and innovation capability. A research by Cater, Prasnikar, & Cater (2009) found that most of companies are environmentally responsible because of the personal commitment from the top management. Furthermore, it also reveals that public concern is a least important motive in implementing environmental management strategy, for the consumer's demands for the level of environmental friendliness is considered insufficient to be the main motives in practicing environmental strategy.…”
Section: Environmental Management Strategymentioning
confidence: 99%
“…Tindakan yang dapat dilakukan adalah dengan memahami secara benar karakter bisnis, lingkungan dan personil yang dimiliki oleh suatu industri. Sejumlah upaya dilakukannya untuk perbaikan kinerja manajemen telah dijelaskan pada beberapa studi sebelumnya yaitu (Holtkamp, 2022;Kaharti, 2021;Nguyen dkk., 2018;Sandalgaard & Bukh, 2013;Batt, dkk., 2021;Biswan & Widianto, 2019).…”
Section: Pendahuluanunclassified
“…Misalnya, mengapa anggaran masih banyak digunakan jika tidak sesuai dengan lingkungan bisnis saat ini? Selain itu, keunggulan target kinerja relatif dalam literatur Beyond Budgeting dapat mempengaruhi penerapan model secara universal (Biswan & Widianto, 2019).…”
Section: Kajian Literaturunclassified
“…The grand theory that underlies this research is the inefficiency of budgeting for charter vessels related to budgeting theory and the absence of a reference standard for vessel technical specifications in determining the need for ships supporting oil and gas operations in Indonesia. Biswan and Widianto stated that budgets can translate general and abstract plans, fulfill the concept of responsibility accounting, allocate budget for priority activities, and identify organizational limitations and constraints [3].…”
Section: Introductionmentioning
confidence: 99%